Modelo de mistura padrão com tempos de vida exponenciais ponderados - Gouveia, Bruno Pauka (2010)
In this work, we brie_y introduce the concepts of long-term survival analysis. We dedicated ourselves exclusively to the standard mixture cure model from Boag (1949) and Berkson & Gage (1952), showing its deduction and presenting the imunes probability function, which is taken from the model itself and we investigated the identi_ability issues of the mixture model. Motivated by the possibility that a experiment design can lead to a biased sample selection, we studied the weighted probability distributions, more speci_cally the weighted exponential distributions family and its properties. We studied two distributions that belong to this family; namely, the length biased exponential distribution and the beta exponential distribution. Using the GAMLSS package in R, we made some simulation studies intending to evidence the bias that occur when the possibility of a weighted sample is ignored.